Electro-analytical comparison of commercial mono-crystalline silicon and PERC solar cells to maximize performance. (5th November 2020) - Tripathi, Brijesh; Mahapatra, Apurba; Verma, Deepak; Kalam, Abul; Pandey, Manoj Kumar; Trivedi, Suverna; Kumar, Manoj
Abstract: In this article detailed electro-analytical comparison of the commercial mono-crystalline silicon and passivated emitter and rear contact (PERC) solar cells has been presented that can help in device optimization during manufacturing process. This study indicates fundamental differences between these two technologies in terms of the series resistance, shunt resistance and junction quality including ideality factor and doping concentration. Impedance spectroscopic analysis revealed a value of series resistance of 1 Ω for both the devices with no substantial difference, which suggest that employed metal contacts and base layer conductivity in both the solar cells have comparable electrical characteristics. The shunt resistance of 190 Ω cm 2 and 98 Ω cm 2 have been obtained for PERC and reference solar cells. The ideality factors of 1.9 and 2.2 have been obtained for PERC and reference solar cells, which indicate a better junction quality in PERC solar cells. From Mott-Schottky analysis a value of 0.65 V built-in potential has been obtained for both the solar cells. A doping density of 2.31 × 10 16 cm −3 and 4.494 × 10 16 cm −3 has been obtained for reference and PERC solar cells. This study intends to provide a basis for development of better optimization strategies to improve the performance of solar cells.